2010
DOI: 10.1136/jamia.2010.005637
|View full text |Cite
|
Sign up to set email alerts
|

Health information technology: fallacies and sober realities

Abstract: Current research suggests that the rate of adoption of health information technology (HIT) is low, and that HIT may not have the touted beneficial effects on quality of care or costs. The twin issues of the failure of HIT adoption and of HIT efficacy stem primarily from a series of fallacies about HIT. We discuss 12 HIT fallacies and their implications for design and implementation. These fallacies must be understood and addressed for HIT to yield better results. Foundational cognitive and human factors engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
229
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(238 citation statements)
references
References 87 publications
(27 reference statements)
4
229
0
5
Order By: Relevance
“…Stavri and Ash [13] suggested that success is often preceded by failure. Indeed, all the information collected and analyzed during this survey was useful for re-implementation of the CPOE system at RUH and helped to prevent HIT fallacies [35]. As a consequence, the budget of the information systems department has been substantially raised to allow for complete reorganization, better documentation and purchase of new servers.…”
Section: Cpoe Was Never Perceived As Superior To Pboe Qualitative Anmentioning
confidence: 99%
“…Stavri and Ash [13] suggested that success is often preceded by failure. Indeed, all the information collected and analyzed during this survey was useful for re-implementation of the CPOE system at RUH and helped to prevent HIT fallacies [35]. As a consequence, the budget of the information systems department has been substantially raised to allow for complete reorganization, better documentation and purchase of new servers.…”
Section: Cpoe Was Never Perceived As Superior To Pboe Qualitative Anmentioning
confidence: 99%
“…Furthermore, the information generated and retrieved from inadequately conceptualized eHealth is often not helpful for health care management decision-making (Kaye et al, 2010), because information is not applicably clustered; it is frequently disparate with predefined indicators, while modalities and jurisdiction on management and transaction of information can be ambiguous and unrelated to priority tasks and functions of health care professionals (Heeks, 2006;Ibrahim et al, 2013). In other words, poorly defined and unstructured eHealth projects have a tendency to be data and information driven, instead of action driven (Karsh et al, 2010). In order to avoid these threats, the entire eHealth project, including its long-term and wide-ranging implications, must be well thought out, while its contextual role and functions within the health care system must be clearly defined (Haux et al, 2008;Kanjo, 2011), yet flexible and adaptable to requirements and continuous changes in health care ecosystem and broader social environment.…”
Section: Ehealth Implicationsmentioning
confidence: 99%
“…Notwithstanding the potential of HISs, in practice, the collection, compilation, analysis, and reporting of health data are riddled with major problems [5,26,27]. Furthermore, the data received are often not helpful for healthcare management decision-making because they are incomplete, untimely, and unrelated to the priority tasks of healthcare professionals [28][29][30].…”
Section: Introductionmentioning
confidence: 99%